2016
DOI: 10.15835/nbha44210475
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aqueous Extracts of Sticky Willy (Galium aparine L.) on the Growth of Seedlings of Selected Maize Varieties (Zea mays L.)

Abstract: In the environment plants are competing for water, nutrients and light, and other components. Their competition is not only based on shading but on the allelopathic interactions as well. Sticky willy (Galium aparine L.) is a nitrophilous weed growing in thickets, crop fields and on ruderal areas. Its sticky and strongly branching stems are connecting together stalks of grain make it difficult to harvest. G. aparine wraps around plants and limits their access to the light. It may to secrete allelopathic substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…If the seedling root is in the suitable conditions for growth, it gets the substances needed for the development. Otherwise, the surrounding environment causes disturbances in the absorption capacity of water and (Pula et al, 2016). During this experiment, it was found that aqueous extracts of Mentha × piperita leaves, regardless of concentration, clearly limited seed germination.…”
Section: Discussionmentioning
confidence: 72%
“…If the seedling root is in the suitable conditions for growth, it gets the substances needed for the development. Otherwise, the surrounding environment causes disturbances in the absorption capacity of water and (Pula et al, 2016). During this experiment, it was found that aqueous extracts of Mentha × piperita leaves, regardless of concentration, clearly limited seed germination.…”
Section: Discussionmentioning
confidence: 72%
“…For example: Możdżeń et al (2016) showed the inhibitory e ect of aqueous extracts from Capsella bursa-pastoris (L.) Medik. on germination and growth of Lactuca sativa L. cv 'Maryna' , Puła et al (2016) studied the e ect of aqueous extracts of Galium aparine L. on various cultivars of Zea mays L., Możdżeń et al (2018) observed the allelopathic activity of Galinsoga parvi ora Cav. and Oxalis fontana Bunge on early growth stages of di erent cultivars of Raphanus sativus L. var.…”
Section: Discussionmentioning
confidence: 99%